Pengukuran Mutu Layanan Kesehatan Dasar Gratis Sebagai Perwujudan Hak Sehat Bagi Masyarakat Sukoharjo - Sri Nugroho, Arif Julianto; PRASETYO, Jarot; Nursito, Sarwono (KIAT BISNIS, 2013)
In order to increasing publicâs welfare, especially in health, Sukoharjo regent made one policy tocreate primary health service charge of free in community health center to the public withoutdifferentiate the socioeconomic status, with 2009 decision Letters of Sukoharjo Regent, No 02. Inperforming this policy, there is much problem both technical and operational. This research isaimed at investigating external people satisfaction in public health care services, Dinas KesehatanKabupaten Sukoharjo, 100 people are chosen as samples with Servqual model.The researchillustrates that the Servqual model as a useful managerial tool can be applied in identifying areasto which management resources should be allocated in order to improve and enchance the qualityof service the Dinas Kesehatan Intitution. The result shows that most servqual modelfactors:tangibles, reliabilities, assurance, responsiveness, empathies are less satisfied than itshould be.Keywords : community health center, servqual, satisfaction